AKTIVITAS FISIK PADA LANSIA MENINGKATKAN FUNGSI KOGNITIF KESEIMBANGAN DAN KUALITAS HIDUP STUDI EKSPERIMENTAL DI JAKARTA - Yvonne Suzy Handajani, Nelly Tina Widjaja, Yuda Turana, Poppy Kristina Sasmita (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION FALLS IN THE ELDERLY ARE COMMON AND ASSOCIATED WITH DECLINING IN BALANCE FUNCTION THAT IS INFLUENCED BY MANYFACTORS SUCH AS MOTOR AND SENSORY SYSTEMS AND COGNITIVE FUNCTION RESEARCH HAS SHOWN EFFECTIVITY OF PHYSICAL EXERCISE PROGRAM DESIGNED TO REDUCE FALLS TO IMPROVE QUALITY OF LIFE AND TO ENHANCE COGNITIVE FUNCTIONS